1996
DOI: 10.1246/bcsj.69.1223
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Characterization of 9,10-Diethyl-9,10-diphospha-9,10-dihydroanthracene as an Electron Donor

Abstract: The molecular structure of 9,10-diethyl-9,10-diphospha-9,10-dihydroanthracene (PEPP) was determined by X-ray analysis. The central six-membered ring takes a boat conformation with two phosphorus atoms being the stem and stern, and the condensed tricyclic skeleton forms a butterfly-like structure. Of the two ethyl groups, which are attached to two P atoms in the central ring, the one is placed toward outside the skeleton (extra), and the other is located toward the inside of the ‘butterfly’ (intra). The observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…They showed that the dibenzo[b,b]1,4‐dihydro‐1,4‐diphosphinines IIa , b (a: R = Ph; b: R = Et) could be obtained by stepwise, base‐initiated ring closure using dichloro(organo)phosphanes. Later on, Uchida added a further simplification to the synthetic protocol of IIb . The synthesis of I was achieved by Märkl by the reaction of diethynylphosphane with a primary phosphane, which led to new P‐substituted derivatives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that the dibenzo[b,b]1,4‐dihydro‐1,4‐diphosphinines IIa , b (a: R = Ph; b: R = Et) could be obtained by stepwise, base‐initiated ring closure using dichloro(organo)phosphanes. Later on, Uchida added a further simplification to the synthetic protocol of IIb . The synthesis of I was achieved by Märkl by the reaction of diethynylphosphane with a primary phosphane, which led to new P‐substituted derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, compound IV was obtained by the thermal reaction of the corresponding backbone, dichlorophosphanyl‐substituted 1‐methyl‐2‐alkyl‐imidazole, with pyridine (as the base), thus leading to the tricyclic heterocyclic scaffold shown in Figure . Hitherto, surprisingly few reactivity studies have been reported on mono‐, bi‐, or tricyclic 1,4‐dihydro‐1,4‐diphosphinines relying exclusively on derivatives possessing exocyclic P–C single bonds,, thus significantly restricting the opportunities of P functionalization.…”
Section: Introductionmentioning
confidence: 99%
“…The 1,4‐dihydro‐1,4‐diphosphinines, though well‐known since 1964, reactivity studies have received little attention. Recently, we reported on a new class of imidazole‐2‐thione‐based tricyclic 1,4‐dihydro‐1,4‐diphosphinines and their conversion into 1,4‐diphosphinines using dedichlorination under mild conditions .…”
Section: Introductionmentioning
confidence: 99%
“…1 H (400 MHz) and 13 C (100 MHz) NMR spectra were recorded on a JEOL EX400 spectrometer, and samples were analyzed in CDCl 3 using tetramethylsilane as an internal standard. Elemental analyses were performed at the Microanalytical Center of Kyoto University.…”
Section: Experimental Generalmentioning
confidence: 99%
“…The 1,4-dihydro-1,4-diarsinines are stable toward air and moisture. Cyclic organophosphorus [12] or organonitrogen [13][14][15][16] compounds, which are similar analogues of 1,4-dihydro-1,4-diarsinines, are too redox-active as ligands because of their two ethylene bridges. On the other hand, cyclic organoarsenic compounds similar to cis-1,4-dihydro-1,4-diarsinines such as 5,l0-dihydroarsanthren were synthesized [17].…”
Section: Introductionmentioning
confidence: 99%